(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article describes the use of special games to increase the level of general and special physical fitness of young sambo wrestlers, to increase functional and basic physical fitness, develop competition skills, improve tactical thinking, increase the ability to compete in difficult situations, and use non-traditional methods quickly. The methods that develop the possibilities of implementation are shown.